2022
DOI: 10.3389/fendo.2022.829175
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Lactate Metabolism-Related lncRNA Signature as a Prognostic Model for Lung Adenocarcinoma

Abstract: BackgroundLung cancer has been a prominent research focus in recent years due to its role in cancer-related fatalities globally, with lung adenocarcinoma (LUAD) being the most prevalent histological form. Nonetheless, no signature of lactate metabolism-related long non-coding RNAs (LMR-lncRNAs) has been developed for patients with LUAD. Accordingly, we aimed to develop a unique LMR-lncRNA signature to determine the prognosis of patients with LUAD.MethodThe Cancer Genome Atlas (TCGA) and Gene Expression Omnibus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 75 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…Metabolism-related lncRNAs have been demonstrated to play an important role in regulating cancer metabolism and the crosstalk between cancer metabolism and tumor microenvironment (17). Previous studies have also discovered a series of lncRNA biomarkers or signatures related to metabolism for lung cancer based on bioinformatics analysis (18)(19)(20). However, limited research has explored molecular subtypes and prognostic biomarkers based on lncRNAs related to pentose phosphate pathway that is one of metabolism pathways involved in cancer development (21).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolism-related lncRNAs have been demonstrated to play an important role in regulating cancer metabolism and the crosstalk between cancer metabolism and tumor microenvironment (17). Previous studies have also discovered a series of lncRNA biomarkers or signatures related to metabolism for lung cancer based on bioinformatics analysis (18)(19)(20). However, limited research has explored molecular subtypes and prognostic biomarkers based on lncRNAs related to pentose phosphate pathway that is one of metabolism pathways involved in cancer development (21).…”
Section: Introductionmentioning
confidence: 99%
“…In BC, lactate is correlated with resistance to PI3K inhibitors ( Hillis and TOKER, 2020 ). In several cancers, lactate is essential in predicting prognosis, tumor microenvironment, and immune response ( Mai et al, 2022 ; Sun et al, 2022 ; Xie et al, 2022 ). However, the prognostic value of lactate in BC remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that elevated lactic acid produced by Warburg effect is a poor prognostic indicator for metastatic lung cancer 9 . The effect of lactate has also been established and confirmed in the prognosis of colorectal cancer, 10 lung adenocarcinoma, 11 and esophageal squamous cell carcinoma 12 . Moreover, recent research has demonstrated that Warburg effect‐related genes have a significant effect on tumor progression and prognosis.…”
Section: Introductionmentioning
confidence: 94%